Insight into the inhomogeneous capacity distribution characteristic of LiFePO4 cathode in large-format lithium ion cell. Issue 7 (1st April 2021) - Zhuang, Shuxin; Jia, Deli; Wang, Quanbin; Hu, Yongfeng; Zhang, Minshu; Li, Xiaodan; Lin, Jianping; Wu, Qihui; Zhou, Jigang; Lu, Mi
Abstract: The inhomogeneous capacity degradation distribution of large-format LiFePO4 -based lithium ion cell after 2500 charge-discharge cycles is analyzed via the selected regions of the cathodes using half-cell charge-discharge test, high resolution transmission electron microscopy, X-ray photoelectron spectroscopy and X-ray absorption spectroscopy analysis. The results showed that the initial specific charge capacities demonstrate an obvious position-dependent characteristic, indicating inhomogeneous reactions occurring on the electrode. The low initial charge capacities near the tab location can be recovered after discharging, indicating the capacity degradation is from the active lithium loss, rather than the crystal structure destruction. The X-ray photoelectron spectroscopy and high resolution transmission electron microscopy results further verified these deduction and the X-ray absorption spectroscopy analysis results indicate that the difference on the structure change of LiFePO4 is mainly at the surface, rather than in the bulk.